Context-based vocational didactics - Hamid Asghari; Anna Öhman (Scandinavian Journal of Vocations in Development)
The aim of this special issue, which includes 16 articles featuring research from Sweden, Norway, Denmark, and Finland, is to deepen and clarify the understanding of context-based vocational didactics, which continuously evolves with societal changes and technological advancements. The articles address various aspects of vocational didactics, including support for students with special needs, the role of digitalisation, and the collaboration between school and working life. This special issue emphasises the importance of adapting teaching to a changing labour market and education system, as well as preparing students for both professional life and as democratic citizens.